2008
DOI: 10.1016/j.dental.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a bonding agent on in vitro biochemical activities of remineralizing resin-based calcium phosphate cements

Abstract: Compared to the control all treatments resulted in mineral increase. The remineralization was negatively affected by the presence of the bonding agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 12 publications
1
42
0
Order By: Relevance
“…In vitro [6,7] and in vivo [3,4] studies demonstrated that remineralisation may be achieved by increasing the mineral content and the mechanical properties (i.e. hardness and modules of elasticity) of dental hard tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro [6,7] and in vivo [3,4] studies demonstrated that remineralisation may be achieved by increasing the mineral content and the mechanical properties (i.e. hardness and modules of elasticity) of dental hard tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the purpose of the present study was to determine if biomimetic analogs may be incorporated in MTA, a clinically-acceptable, radiopaque Portland cement-based material for remineralization of artificial caries-like dentin. Specifically, as dentin remineralization with calcium phosphate resin cements is adversely affected by dentin adhesive application [30], the effects of dentin remineralization with biomimetic analogs-incorporated MTA in the presence or absence of dentin bonding were evaluated. The null hypothesis tested was that the dentin remineralization efficacy of MTA in simulated body fluid is not affected by the incorporation of biomimetic analogs or adhesive application.…”
Section: Introductionmentioning
confidence: 99%
“…Remineralization of residual affected dentin can be promoted by the use of bioactive, ionreleasing base materials, e.g., glassionomer or resinbased calciumphosphate cements (RCPC) (Mukai et al, 1998;Dickens et al, 2003Dickens et al, , 2004Exterkate et al, 2005;Ngo et al, 2006). In vitro remineralization experiments with RCPC resulted in significantly increased mineral content, documenting the capacity of RCPC to remineralize and promote healing of mineraldeficient dentin (Dickens et al, 2003;Dickens and Flaim, 2008). A subsequent in vivo proofofprinciple study (Peters et al, 2010) reported increased hardness, evaluated clinically, and increased mineral content, which was determined by elemental analysis of RCPCtreated caries affected dentin.…”
Section: Introductionmentioning
confidence: 99%